Good Corporate Governance dan Manajemen Laba Pada Kinerja Keuangan - Mahayadi, Putu Satria; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2024)
Financial performance is a measurement used by managers and investors to measure the level of productivity and financial soundness of a company. This study aims to examine the effect of good corporate governance and earnings management on the financial performance of state-owned companies listed on the IDX in 2019-2022. This research was conducted on 20 companies listed on the IDX in 2019-2022 by accessing the official website of the Indonesia Stock Exchange and the official website of each company. The sample in this study was determined by purposive sampling technique. Data were analyzed using multiple linear regression. The results of the analysis show that good corporate governance and earnings management have a positive effect on the financial performance of state-owned companies listed on the IDX in 2019-2022.